Routledge handbook of Theravāda Buddhism - Berkwitz, Stephen C.; Thompson, Ashley (Routledge, 2022)
INTRODUCTION / Stephen C. Berkwitz & Ashley Thompson -- PART I: Ideas/Ideals 1. "THERAVĀDA": Sectarianism and Diversity in Mahāvihāra Historiography / Sven Bretfeld -- 2. PĀLI: Its Place in the Theravāda Buddhist Tradition / Alastair Gornall -- 3. CIRCULATIONS: Linked Spaces and Divergent Temporalities in the Pāli World / Anne M. Blackburn -- 4. STATECRAFT: From Buddhist Kingship to Modern States / Patrice Ladwig -- 5. REFORM: Ideas and Events in Modern Theravāda Reformism / Anne Hansen & Anthony Lovenheim Irwin -- 6. TRADITION: Nuns and "Theravāda" in Sri Lanka / Nirmala Salgado -- PART II. Practices/Persons: 7. MERIT: Ritual Giving and Its Cultural Meditations / Juliane Schober -- 8. MEDITATION: Techniques and Processes of Transformation / Pyi Phyo Kyaw & Kate Crosby -- 9. REPETITION: Pāli Iterations of Ritual Commitment, Commentarial Refrain, and Assiduous Practice / Christoph Emmrich -- 10. FILIAL PIETY: Shades of Difference across Theravādin traditions / Gregory Kourilsky -- 11. LAITY: Status, Role and Practice in Theravāda / Asanga Tilakaratne -- 12. DISCIPLINE: Beyond the Vinaya / Thomas Borchert -- 13. FUNERALS: Changing Funerary Practices / Katherine Bowie -- PART III. Texts/Teachings: 14. CANONS: Authoritative Texts of the Theravaṃsa / Peter Skilling -- 15. ABHIDHAMMA: Theravāda Thought in Relation to Sarvāstivāda Thought / Rupert Gethin -- 16. VAṂSA: History and Lineage in the Theravāda / Stephen C. Berkwitz -- 17. MERIT: Ten Ways of Making Merit in Theravāda Exegetical Literature and Contemporary Sri Lanka / Rita Langer -- 18. BILINGUALISM: Theravāda Bitexts across South and Southeast Asia / Trent Walker -- PART IV. Images/Imaginations: 19. VISUAL NARRATIVES: Buddha Life Stories in the 'Medieval Theravāda' of Southeast Asia / Samerchai Poolsuwan -- 20. ICONS: Standing out from the Narrative in Theravādin Art / Ashley Thompson -- 21. AFFECT: Notes from Contemporary Southeast Asian Visual Culture / Chairat Polmuk -- 22. DEITIES: Supernatural Forces in Theravāda Buddhist Religious Cultures / John Holt -- 23. MONS: Creating a Narrative of the Origins of Theravāda / Patrick McCormick.